Understanding place holistically: Cities, synergistic relationality, and space syntax - Seamon, David (My University, 2017)
This article discusses two contrasting conceptual understandings of place. The approach of analytic relationality interprets places as sets of interconnected parts and their relationships. In contrast, synergistic relationality interprets places as integrated, generative fields, the parts of which are only parts as they both sustain and are sustained by the constitution and dynamism of the particular place as a whole. This article presents one interpretation of place as synergistic relationality by describing six interrelated, generative processes: place interaction, place identity, place release, place realization, place creation, and place intensification. The article considers how concepts and principles relating to space syntax contribute to understanding places as synergistic relationality broadly; and to understanding the six place processes specifically.
Citation: Seamon, D. (2015). Understanding place holistically: Cities, synergistic relationality, and space syntax. The Journal of Space Syntax,6(1), 19-33. http://joss.bartlett.ucl.ac.uk/journal/index.php/joss/article/view/246
Keywords: Holistic science; Phenomenology of place; Place; Relational ontologies; Relationality; Space syntax